Pengaruh Model Perolehan Konsep Dengan Metode Demonstrasi Terhadap Penguasaan Konsep Fisika Siswa SMA - Atikatun Hulwani; Susilawati Susilawati; Kosim Kosim (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2019)
This study aims to analyze the effect of the concept attainment model with the demonstration method on the mastery of student physical concepts. This type of research is a quasi-experimental with pre-test and post-test control group design. The population in this study were all students of class XI MIPA in one of the state high schools in West Lombok. The sampling technique in this study used a purposive sampling technique, so that the sample used in the study was class XI MIPA 3 as an experimental class and class XI MIPA 6 as a control class. The instrument used in this study was in the form of multiple choice questions totaling 21 items. The pre-test results show that the average value of the experimental class is 37,3 and the control class is 35,9. Data analysis techniques using t-test with pre-test and post-test, so that the results of the hypothesis test conducted at the final test obtained t-count of 2,250 and t-table of 2,012. Because t-count is greater than t-table, it can be concluded that H0 is rejected, it means that the concept attainment model with the demonstration method affects the mastery of the physics concepts of high school students.